High speed servo control of multi-axis machine tools - Renton, Douglas D.A. (My University, 2000)
High Speed Servo Control of Multi-Axis Machine Tools, is concerned with maintaining tight position control at high feed rates, in the presence of disturbances generated by the cutting process. This is an important goal due to general advances in machining technologies, as well as economic pressures in specific industries. In this thesis a feed rate planning method, and servo loop control law are developed which explicitly account for the dominant machine tool servo characteristics, including actuator saturation. The feed rate planning method developed, 'Minimum Time Path Optimization' (MTPO), enables coordinated motions to be planned with near maximum utilization of servo capabilities (a reserve must be left to handle modeling error, and disturbances). The result is a significant reduction in servoing time without sacrificing path accuracy when compared to fixed acceleration and velocity limit path planning, or significantly reduced path error, when compared to fixed feed rate planning (assuming equal total time time). The servo loop level controller developed, Minimum-Time Tracking Control (MTTC), focuses on the primary sources of path error in high-speed servoing applications, specifically, limits on amplifiers, system inertia, and damping. This controller is relatively simple to compute, making it suitable for high speed servo control. MTTC's advantages are most clearly seen in its consistently superior disturbance-rejection properties. MTTC is shown to regulate steps of various sizes better (faster/less over shoot) than Generalized Predictive Control (GPC), H∞ , or Proportional Derivative (PD) controllers. It is also shown to respond more linearly in magnitude, and phase (unity gain, zero lag) to sin waves at various frequencies. A periodic observer is developed and implemented which significantly improves the rejection of cutting disturbances. Given that the major source of disturbances is the cutting process, an encoder on the spindle is used to synchronize compensation, with the disturbance. The instantaneous disturbance is estimated as the difference between the predicted acceleration, and the achieved acceleration. This estimate is then averaged as a function of spindle position, over successive spindle revolutions. A linear servo motor is constructed to investigate commutation strategies which allows each winding of a permanent magnet linear motor to be driven separately. This enables commutation strategies to be implemented which reduce the heat generated in the coils of the linear motor, increasing the continuous holding force of the motor by approximately 18%. A PC based Open Architecture Control (OAC) with soft motion control is developed which provides low level openness (All calculations including closing servo loops are performed on the PC, no special purpose motion control card is used.). This system enables the developed controllers, observers, and commutation strategies to be implemented in a cost efficient manner. It also eliminates many of the machine controller limitations which make path planning and computing difficult. Specifically, it enables the entire part path to be planned and computed in advance, stored, and executed, or played back in real-time. This eliminates the requirements of bounded execution times, and the difficulty of representing data in an intermediate form.
Keywords: Mechanical Engineering; Mechanical Engineering